The Extent to which Chemistry Teachers Practice Teaching Strategies Related to Metacognitive Thinking and the Direction Towards the Teaching Profession at the Secondary Stage in Jordan - Shnnag, Al-Majid Kamal; Almomani, Jehad Ali (Journal of Educational and Psychological Sciences, 2021)
This study, which followed the descriptive analytical approach, aimed to identify the extent to which chemistry teachers practice teaching strategies related to metacognitive thinking and the direction towards the teaching profession at the secondary stage in Wadi Al-Seer schools and the relationship of these strategies to teacher attitudes Chemistry about the teaching profession. The researcher used two tools to achieve the objectives of this study, one of which was a questionnaire that included teaching strategies related to metacognitive thinking that consisted of 27 paragraphs, and the other was a measure of attitudes toward the teaching profession. Its number reached 28 items, where it was applied to the study members after verifying its validity and reliability. The results have shown, after analyzing the data of the responses of the sample members, that the extent of study members practicing metacognitive thinking strategies was average, as well as the presence of positive attitudes of the study members’ towards the teaching profession and with a high degree. The results also showed a statistically significant correlation relationship at the level of significance (0.05) between the extent of study members’ practice of teaching strategies and their attitudes towards the teaching profession, and there are statistically significant differences in the chemistry teachers’ practice of the teaching strategy related to metacognitive thinking attributable to both sex variable and in favor of female teachers, sector variable and in favor of the private sector, and experience variable and in favor of individuals from the years of experience category less than five years. In light of the results, the study recommended the necessity of preparing and developing training programs for teachers and encouraging them to use metacognitive teaching strategies and apply them in educational situations.